Experimental Economics on Firm’s Behavior: Entry Game Approach - Sukadana, I Wayan; Saraswaty, Amrita Nugraheni (Jurnal Ekonomi Kuantitatif Terapan; 2014: Vol. 7, No. 2, Agustus 2014 (pp. 83-198)DO - 10.24843/JEKT.2014.v07.i02.p05, 2015)
The paper analyzes subject’s behavior in evolutionary process of entry game. The experiment is designed to analyze the behavior of the subject. The experiment is set in sequential entry games. Process of the game was conducted under asymmetric information, uncertainty, payoff perturbation and random matching. The subjects of the experiment were students of the Universitas Udayana, Bali, Indonesia. Subjects who play as new-entrance firms tend to choose “stay-out” strategy when the uncertainty and the amount of loss increase. Meanwhile, the subjects who play as an incumbent firm, which set to have more information about the game (market) rather than the new-entrances, most of the time abuse their position by choose “threat” strategy, which not a credible strategy for some of them. Experimental studies shows that New-entrance tend to weight more on lost when the risk increase (from risk averse setting to risk seeking setting), and tend to choose sure value over a lotteries although the expected value from lotteries is higher or the same. These findings support the reason that Indonesian youngsters tend to choose a job as a PNS or employee of existing firms. The results also support the reason that Indonesian businessman is more willing to open a new business if they have a guarantee for their losses.
Keywords: entry game, experiment, asymmetry information, lost aversion